The pumping parameters for Er-doped tellurite glass - Sahar, Md. Rahim (2013)
Erbium doped tellurite glass rod of the 78.5 TeO2 - 20 ZnO - 1.5 Er2O3 where has successfully been fabricated as lasing medium and have been investigated by means of their properties needed in lasing application. The external triggering method is used to generate high peak current in several microsecond pulse duration. The external triggering circuit design consists of power supply, discharge capacitor, control unit, pulse forming network and ignition circuit. This driver operates in single mode pulse that can be adjusted corresponding to the controller which can vary from 650V to 1000V. The operation is started initially with an external trigger pulse which is the voltage pulse of 8kV with pulse duration 20.0μs. The connection operated by trigger thrystor (SCR) as a switch and ionized gaseous inside the lamp. After the gaseous breakdown, the current from the capacitor flows continuously through the flashlamp. The output current is initially increased proportion in order to the input energy. Maximum value of peak current flashing at 888A with higher input energy, while, the increasing voltage is not linearly increased with the input energy. From the plotted graph of current and voltage, V-I, shows a nonlinear relationship with the electrical input energy. The developed flashlamp driver has produced about 87% in efficiency while another 13% is lost in the circuit resistance. Flashlamp radiation is detected by using spectrometer in the range of 200nm to 1000nm. The beam is used to excite the erbium glass medium and a coherent beam of 1550nm wavelength is produced.